PENGARUH KUALITAS LAYANAN, CITRA BANK DAN KEPERCAYAAN TERHADAP KEPUASAN NASABAH TABUNGAN SIMPEDA BANK JATENG CABANG UTAMA SEMARANG - Cavalera, Niel Dhesta; Soliha, Euis (Proceeding SENDI_U, 2019)
This study aims to examine and analyze the influence of service quality, bank image and trust incustomer satisfaction Simpeda Central Java Bank savings Semarang Main Branch. This research wasconducted at the Central Java Bank Semarang Main Branch with a total sample of 100 respondents. Datacollection was done through a questionnaire with measurements using the Likert Scale five alternative answers.Non probability sampling sampling technique with purposive sampling data collection method. Purposivesampling criteria, namely respondents with a minimum age of 17 years, at least have become customers of BankJateng for one year and at least have done transactions three times. The data analysis technique used is linearregression analysis, while to test the hypothesis using the t test. Service quality has a positive and significanteffect on customer satisfaction, the image of the bank has a positive and significant effect on customersatisfaction, trust has a positive and significant effect on customer satisfaction.